2015
DOI: 10.1038/cr.2015.22
|View full text |Cite
|
Sign up to set email alerts
|

p53 isoform Δ113p53/Δ133p53 promotes DNA double-strand break repair to protect cell from death and senescence in response to DNA damage

Abstract: The inhibitory role of p53 in DNA double-strand break (DSB) repair seems contradictory to its tumor-suppressing property. The p53 isoform ∆113p53/∆133p53 is a p53 target gene that antagonizes p53 apoptotic activity. However, information on its functions in DNA damage repair is lacking. Here we report that ∆113p53 expression is strongly induced by γ-irradiation, but not by UV-irradiation or heat shock treatment. Strikingly, ∆113p53 promotes DNA DSB repair pathways, including homologous recombination, non-homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
136
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(147 citation statements)
references
References 48 publications
9
136
0
2
Order By: Relevance
“…Our recent finding demonstrated that Δ133p53 promotes DNA DSB repair by upregulating the expression of RAD51, LIG4 and RAD5221. Therefore, we checked the protein accumulation of these three genes in reprogramming at 12 dpi using Western blot (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent finding demonstrated that Δ133p53 promotes DNA DSB repair by upregulating the expression of RAD51, LIG4 and RAD5221. Therefore, we checked the protein accumulation of these three genes in reprogramming at 12 dpi using Western blot (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, we demonstrate that Δ133p53 is strongly induced by DNA DSBs and not only inhibits cell apoptotic activity, but also promotes all three DNA DSB repair pathways to protect cells from death and DNA damages upon γ-irradiation. Δ133p53 promotes DNA DSB repair via up-regulating the transcription of the three DNA DSB repair genes: RAD51 , LIG4 and RAD52 , independent of p5321.…”
mentioning
confidence: 99%
“…Another possibility is that Δ133p53 may directly upregulate the neurotrophic factors NGF and IGF-1 through its gain-of-function activity, which was recently reported to activate a set of genes for DNA damage repair. 59 Although in silico analysis of the NGF and IGF-1 gene promoters did not identify a perfect match to the predicted Δ133p53-binding response element, 59 further studies will elucidate the regulation of these neurotrophic factors by Δ133p53 in dominant-negative and gain-of-function manners.…”
Section: Discussionmentioning
confidence: 99%
“…7 In this recent study, our original idea was to investigate whether ∆113p53 is induced in response to other stresses. 6 Interestingly, we found that zebrafish Δ113p53 is strongly induced only by γ-irradiation, but not by ultra violet (UV) irradiation and heat shock treatment, whereas full-length p53 is activated by all of three means. Upon γ-irradiation, the patterns of p53 and Δ113p53 protein accumulation were different.…”
Section: Please Scroll Down For Articlementioning
confidence: 96%
“…6 Both of zebrafish ∆113p53 and its human counterpart ∆133p53 are transcribed from an alternative p53 promoter in intron 4. 7,8 Our previous study demonstrated that ∆113p53 is a p53 target gene and strongly induced by γ-irradiation and DNA damage drugs such as camptothecin and roscovitine.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%